A COMPARATIVE STUDY FOR NATURAL DEGRADATION OF THREE LOCAL ANESTHETIC DRUGS FOR HUMAN USE BY ¹H NMR RELAXOMETRY AND FT-IR SPECTROSCOPY - DRĂGAN, L. R.; CRAINIC, R.; FECHETE, R. (Studia Universitatis Babeș-Bolyai Physica, 2018)
Three anesthetics, lidocaine (xylene), ropivacaine and propofol, with localized area of action while used in human surgery, were investigated by 1H NMR relaxometry and ATR-FT-IR spectroscopy. The injectable liquid anesthetics were then subjected to degradation in natural condition during 36 days by exposure to direct sunlight radiation. The sunlight radiation intensity in the infrared and visible domain as well as UV index was monitored using Adafruit SI1145 breakout board sensor. The temperature and humidity was monitored using a digital DHT11 sensor. The evolution of 1H NMR T2-distributions, IR spectra, pH, refraction index, electric conductivity and total dissolved solids (TDS) show a degradation of studied anesthetics but also in some cases a certain recovery.